Resistance Training for Older Women: Do Adaptive Responses Support the ACSM and NSCA Position Stands? - Cavalcante, Edilaine F.; Kassiano, Witalo; Ribeiro, Alex S.; Costa, Bruna; Cyrino, Letícia T. [UNESP]; Cunha, Paolo M.; Antunes, Melissa [UNESP]; Santos, Leandro Dos; Tomeleri, Crisieli M.; Nabuco, Hellen C. G.; Sugihara-Júnior, Paulo; Fernandes, Rodrigo R.; et al. (Wolters Kluwer, 2023)
Purpose The optimal intensity of resistance training (RT) to improve muscular, physical performance, and metabolic adaptations still needs to be well established for older adults. Based on current position statements, we compared the effects of two different RT loads on muscular strength, functional performance, skeletal muscle mass, hydration status, and metabolic biomarkers in older women. Methods One hundred one older women were randomly allocated to perform a 12-wk whole-body RT program (eight exercises, three sets, three nonconsecutive days a week) into two groups: 8-12 repetitions maximum (RM) and 10-15RM. Muscular strength (1RM tests), physical performance (motor tests), skeletal muscle mass (dual-energy X-ray absorptiometry), hydration status (bioelectrical impedance), and metabolic biomarkers (glucose, total cholesterol, HDL-c, HDL-c, triglycerides, and C-reactive protein) were measured at baseline and posttraining. Results Regarding muscular strength, 8-12RM promoted higher 1RM increases in chest press (+23.2% vs +10.7%, P < 0.01) and preacher curl (+15.7% vs +7.4%, P < 0.01), but not in leg extension (+14.9% vs +12.3%, P > 0.05). Both groups improved functional performance (P < 0.05) in gait speed (4.6%-5.6%), 30 s chair stand (4.6%-5.9%), and 6 min walking (6.7%-7.0%) tests, with no between-group differences (P > 0.05). The 10-15RM group elicited superior improves in the hydration status (total body water, intracellular and extracellular water; P < 0.01), and higher gains of skeletal muscle mass (2.5% vs 6.3%, P < 0.01), upper (3.9% vs 9.0%, P < 0.01) and lower limbs lean soft tissue (2.1% vs 5.4%, P < 0.01). Both groups improved their metabolic profile. However, 10-15RM elicited greater glucose reductions (-0.2% vs -4.9%, P < 0.05) and greater HDL-c increases (-0.2% vs +4.7%, P < 0.01), with no between-group differences for the other metabolic biomarkers (P > 0.05). Conclusions Our results suggest that 8-2RM seems more effective than 10-15RM for increasing upper limbs' muscular strength, whereas the adaptative responses for lower limbs and functional performance appear similar in older women. In contrast, 10-15RM seems more effective for skeletal muscle mass gains, and increased intracellular hydration and improvements in metabolic profile may accompany this adaptation.
Keywords: AGING; INTENSITY; NUMBER OF REPETITIONS; STRENGTH TRAINING